Internet and Technology Addiction 2019
DOI: 10.4018/978-1-5225-8900-6.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Fear of Missing Out

Abstract: Smartphones and the evolution of new ICTs have enabled people, especially the youth, to stay connected to their social and professional network. This has resulted in compulsive checking for status updates and messages, for fear of missing out (FOMO). FOMO, which is a form of internet addiction, has its downside among students. This chapter is an empirical study that seeks to examine the disruptive effect of FOMO on the academic performance of students. Four hundred twenty-two university students were surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is an expected outcome that IA has a strong relationship with FoMO which can be defined as an expanded IA implementation (Tang et al. , 2020) and a type of IA (Wirrko, 2019; Metin-Orta, 2020) in the literature. On the other hand, the study conducted by Vaidya et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an expected outcome that IA has a strong relationship with FoMO which can be defined as an expanded IA implementation (Tang et al. , 2020) and a type of IA (Wirrko, 2019; Metin-Orta, 2020) in the literature. On the other hand, the study conducted by Vaidya et al.…”
Section: Discussionmentioning
confidence: 99%
“…FoMO increases with an increase in students' IA. It is an expected outcome that IA has a strong relationship with FoMO which can be defined as an expanded IA implementation (Tang et al, 2020) and a type of IA (Wirrko, 2019;Metin-Orta, 2020) in the literature. On the other hand, the study conducted by Vaidya et al (2016) suggested that FoMO strongly related to IA and FoMO may trigger IA or problematic usage of the internet.…”
Section: Se Ia and Fomo In Online Learning Environmentmentioning
confidence: 99%